Practical recommender systems - Falk, Kim (Manning Publications, 2019)
Online recommender systems help users find movies, jobs, restaurants--even romance! There's an art in combining statistics, demographics, and query terms to achieve results that will delight them. Learn to build a recommender system the right way: it can make or break your application! Practical Recommender Systems explains how recommender systems work and shows how to create and apply them for your site. After covering the basics, you'll see how to collect user data and produce personalized recommendations. You'll learn how to use the most popular recommendation algorithms and see examples of them in action on sites like Amazon and Netflix. Finally, the book covers scaling problems and other issues you'll encounter as your site grows. About the technology Recommender systems are everywhere, helping you find everything from movies to jobs, restaurants to hospitals, even romance. Using behavioral and demographic data, these systems make predictions about what users will be most interested in at a particular time, resulting in high-quality, ordered, personalized suggestions. Recommender systems are practically a necessity for keeping your site content current, useful, and interesting to your visitors. What's inside>/p> How to collect and understand user behavior Collaborative and content-based filtering Machine learning algorithms Real-world examples in Python About the reader Readers need intermediate programming and database skills. About the author Kim Falk is an experienced data scientist who works daily with machine learning and recommender systems.